Adipocytes and macrophages interplay in the orchestration of tumor microenvironment : new implications in cancer progression - Corrêa, Luís Henrique (2017)
Inflammation has been known as one of the main keys to the establishment and progression of cancers. Chronic low-grade inflammation is also a strategic condition that underlies the causes and development of metabolic syndrome and obesity. Moreover, obesity has been largely related to poor prognosis of tumors by modulating tumor microenvironment with secretion of several inflammatory mediators by tumor-associated adipocytes (TAAs), which can modulate and recruit tumor-associated macrophages. Thus, the understanding of cellular and molecular mechanisms that underlay and link inflammation, obesity, and cancer is crucial to identify potential targets that interfere with this important route. Knowledge about the exact role of each component of the tumor microenvironment is not yet fully understood, but the new insights in literature highlight the essential role of adipocytes and macrophages interplay as key factor to determine the fate of cancer progression. In this review article, we focus on the functions of adipocytes and macrophages orchestrating cellular and molecular mechanisms that lead to inflammatory modulation in tumor microenvironment, which will be crucial to cancer establishment. We also emphasized the mechanisms by which the tumor promotes itself by recruiting and polarizing macrophages, discussing the role of adipocytes in this process. In addition, we discuss here the newest possible anticancer therapeutic treatments aiming to retard the development of the tumor based on what is known about cancer, adipocyte, and macrophage polarization.